2021
DOI: 10.21608/tsnj.2021.198903
|View full text |Cite
|
Sign up to set email alerts
|

Structured Teaching Program's Effect on Knowledge and SelfManagement Behaviors for Hemodialysis Patients

Abstract: Background: Promoting the level of knowledge of patients through education is one of the effective factors in increasing the patient responsibility in eliminating or changing unhealthy behaviors. Also, improving self-management of hemodialysis patients needs empowering the patients through educational program. Aim: to assess the effect of structured teaching program on knowledge and self-management behaviors for hemodialysis patients. Subjects and method: Design: A quasi-experimental (pre-post-test) design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The study findings agreed with Mansouri et al, (2019) [6] , who reported at their study that there were highly statically correlation between patient knowledge and quality of life immediate after and follow up the educational program. Also Ahmed., Abd Elzaher.,& Sabra., (2021) [1] , showed that there was significant positive correlation between quality of life and patient knowledge regarding chronic renal failure disease during the immediate post and follow up phases For correlation between score of total knowledge and physical domain score during study phases the study finding revealed that, there was highly statistically significant positive correlation between patient knowledge scores and physical domain scores during the immediate post and there was statistically significant positive correlation between patient knowledge scores and physical domain scores during preprogram and follow up phase.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings agreed with Mansouri et al, (2019) [6] , who reported at their study that there were highly statically correlation between patient knowledge and quality of life immediate after and follow up the educational program. Also Ahmed., Abd Elzaher.,& Sabra., (2021) [1] , showed that there was significant positive correlation between quality of life and patient knowledge regarding chronic renal failure disease during the immediate post and follow up phases For correlation between score of total knowledge and physical domain score during study phases the study finding revealed that, there was highly statistically significant positive correlation between patient knowledge scores and physical domain scores during the immediate post and there was statistically significant positive correlation between patient knowledge scores and physical domain scores during preprogram and follow up phase.…”
Section: Discussionmentioning
confidence: 99%
“…22 Evidence suggests that education can empower patients by improving their knowledge and skills, leading to better disease management and improved health outcomes in chronic diseases. 17,18 Alanzi et al 23 found that WhatsApp was effective in improving the self-efficacy and knowledge of patients with diabetes, whereas Ahmed et al 24 reported that a structured training program improved the knowledge and self-management behaviors of hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alanzi et al 23 found that WhatsApp was effective in improving the self‐efficacy and knowledge of patients with diabetes, whereas Ahmed et al 24 reported that a structured training program improved the knowledge and self‐management behaviors of hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire was developed by the researcher after pertinent literatures as Ahmed et al, (2021); Hamza et al, (2022). It consisted of 48 items, six items about function of the kidney, four items about risk factors for chronic kidney diseases, seven items about medications that impair kidney function, three items about investigations to determine kidney function, five items about signs and symptoms of chronic kidney diseases, seven items about complications of chronic kidney diseases, ten items about food and fluid restrictions for hemodialysis patients, one item about weight gain between hemodialysis sessions and four items about vascular access care.…”
Section: Patients' Knowledge About Kidney and Chronic Kidney Diseases...mentioning
confidence: 99%